Curable polyolefin composition and cured product
Patent Information
- Application Number
- KR1020237036461
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-03-30
Smart Images

Figure 112023116612804-PCT00005 
Figure 112023116612804-PCT00006 
Figure 112023116612804-PCT00007
Abstract
Description
Technology Field
[0001] The present invention relates to a curable polyolefin composition and a cured product thereof. Background Technology
[0002] Thermal gap fillers are generally used in transport assemblies for the thermal management of batteries in electric vehicles. Batteries perform optimally at 15 to 35°C. High temperatures degrade the battery, reducing its lifespan. Safety is also compromised by high temperatures, leading to potentially fatal runaway reactions. Electrochemical reactions in the battery generate heat, and this heat must be removed using a thermal gel as a gap filler between the battery and the heat sink.
[0003] There is high business interest in silicone-free or reduced-silicone polymer matrix-based gap fillers. Volatile silicone species can condense in unwanted areas at Original Equipment Manufacturer (OEM) manufacturing plants. This can lead to numerous issues related to automotive paintability and the occurrence of paint defects such as "fisheye."
[0004] Patent Document 1 describes a rubber composition comprising a polyisobutylene polymer having allyl radicals at the ends, an organohydrogenpolysiloxane having at least two silicon atom-bonded hydrogen atoms per molecule, and a platinum group metal catalyst, forming a sealing member on the periphery of one side of a polymer electrolyte fuel cell separator.
[0005] Patent Document 2 describes a rubber compound comprising: a rubber having at least two functional groups that can be crosslinked by hydrosilylation; a crosslinking agent composed of a hydrosiloxane or a hydrosiloxane derivative comprising at least two silicon atom-bonded hydrogen groups or a mixture of several hydrosiloxanes or derivatives; a hydrosilylation catalyst; at least one filler; and a coagent that can be crosslinked by hydrosilylation.
[0006] Patent Document 3 describes an alkoxysilyl-substituted organic polymer having a number average molecular weight in the range of 200 to 5,000, having a polymer backbone selected from the group comprising: an organic polymer having an average of at least 1.4 alkenyl groups per molecule; a crosslinking agent having an average of at least 1.4 silicon atom-bonded hydrogen atoms per molecule; a platinum group metal-containing catalyst; and polyolefin polymers prepared by hydrogenating polybutadiene, polyisoprene, polyisobutylene, a copolymer of isobutylene and isoprene, a copolymer of isoprene and butadiene, a copolymer of isoprene and styrene, a copolymer of butadiene and styrene, a copolymer of isoprene, butadiene and styrene, polyisoprene, polybutadiene, or a copolymer of isoprene and styrene, a copolymer of butadiene and styrene, or a copolymer of isoprene, butadiene and styrene. A hydrosilylated curable composition containing an oligomer is described.
[0007] Patent Document 4 describes a polyolefin rubber composition comprising an ethylene / α-olefin / non-conjugated polyene random copolymer, an organopolysiloxane containing an average of less than 1 to 2 silicon atoms-bonded hydrogen atoms in the molecule, and an addition reaction catalyst, which can be compression molded or steam vulcanized into a cured product having heat resistance and surface lubricity.
[0008] However, they do not describe soft materials with good thermal conductivity properties. Prior art literature
[0009] Patent Document 1: U.S. Patent Application Publication US 2003 / 0045615 A1 Patent Document 2: U.S. Patent Application Publication US 2008 / 0315148 A1 Patent Document 3: U.S. Patent Application Publication US 2010 / 0206477 A1 Patent Document 4: U.S. Patent Application Publication US 2014 / 0200297 A1 The problem to be solved
[0010] The object of the present invention is to provide a curable polyolefin composition capable of being cured to form a soft material having good thermal conductivity. The object of the present invention is to provide a cured product in the form of a soft material having good thermal conductivity. means of solving the problem
[0011] The curable polyolefin composition of the present invention comprises the following:
[0012] (A) a polyolefin having at least two aliphatic unsaturated bonds per molecule and a viscosity of less than 2,500 mPa·s at 25°C;
[0013] (B) an organopolysiloxane having at least two silicon atom-bonded hydrogen atoms per molecule in an amount such that the cured product obtained by curing the composition has a Shore OO hardness of less than 80;
[0014] (C) a hydrosilylation reaction catalyst in an amount such that the catalytic metal in this component of the composition is at least 2 ppm in terms of mass units; and
[0015] (D) Thermally conductive filler.
[0016] In various embodiments, component (A) is polybutadiene.
[0017] In various embodiments, component (D) is a thermally conductive filler selected from metals, alloys, nonmetals, metal oxides, metal hydroxides, or ceramics.
[0018] In various embodiments, the content of component (D) is 50 mass% or more of the composition.
[0019] In various embodiments, the curable composition further comprises (E) a filler treatment agent.
[0020] In various embodiments, the content of component (E) is 1 mass% or less of the composition.
[0021] The cured product of the present invention is obtained by curing the curable polyolefin composition described above, and the cured product has a Shore hardness of less than 80.
[0022] In various embodiments, the cured product is characterized by being used between the battery and the heat sink in an electric vehicle. Effects of the invention
[0023] The curable polyolefin composition of the present invention can be cured to form a soft material having good thermal conductivity. The cured product of the present invention is in the form of a soft material having good thermal conductivity.
[0024] definition
[0025] The terms “comprising” or “comprise” signify the concepts of “including,” “include,” “essentially composed of,” and “to be composed of,” and are used herein in their broadest sense to include. The use of “for example,” “eg,” “such as,” and “including” to enumerate exemplary examples is not limited to the enumerated examples alone. Accordingly, “for example” or “such as” means “for example, but not limited to” or “such as, but not limited to,” and includes other similar or equivalent examples. As used herein, the term “about” serves to reasonably include or describe small variations in numerical values measured by instrumental analysis or as a result of sample handling. These small variations may be approximately ± 0 to 25%, ± 0 to 10%, ± 0 to 5%, or ± 0 to 2.5% of the numerical value. Additionally, when the term “approximately” is associated with a range of values, it applies to both numerical values. Furthermore, the term “approximately” may apply to numerical values even when not explicitly specified.
[0026] The term “soft material” is used herein to mean a gel-like material having a Shore OO hardness of less than 80 or a Shore A hardness of less than 25 according to ASTM D 2240.
[0027] Detailed description of the invention
[0028] The curable polyolefin composition of the present invention will be described in detail.
[0029] Component (A) is a main component and is a polyolefin having at least two aliphatic unsaturated bonds per molecule. In the invention, component (A) is a polyolefin grafted onto a main chain group having aliphatic unsaturated bonds or a polyolefin having a main chain containing aliphatic carbon-carbon unsaturated bonds. Component (A) may be linear or branched and may be a homopolymer, copolymer, or terpolymer. Component (A) may also exist as a mixture of different polyolefins, provided that there are at least two aliphatic unsaturated bonds on average per molecule. Examples of polyolefins for component (A) include polyisoprene, polybutadiene, copolymers of ethylene, propylene, isobutylene, and isoprene, copolymers of isoprene and butadiene, copolymers of isoprene and styrene, copolymers of butadiene and styrene, copolymers of isoprene, butadiene, and styrene, and polyolefin polymers prepared by hydrogenation of polyisoprene, polybutadiene, or copolymers of isoprene and styrene, copolymers of butadiene and styrene, or copolymers of isoprene, butadiene, and styrene. Among these, component (A) is preferably polybutadiene.
[0030] The aliphatic unsaturated bonds in the molecule of component (A) may be identical or different and may comprise two or more carbon atoms, preferably 2 to 12 carbon atoms. They may be linear or branched, but linear alkenyl groups are preferred. Examples of suitable groups having aliphatic unsaturated bonds include alkenyl groups, such as vinyl groups, allyl groups, butenyl groups, pentenyl groups, and hexenyl groups, and vinyl and / or allyl groups are particularly preferred. The groups having aliphatic unsaturated bonds may be found as pendants along the polymer chain or at the chain ends, and it is preferable for the groups to be present at the chain ends.
[0031] Component (A) has a viscosity at 25°C of 2,500 mPa·s, preferably in the range of 1 to 2,000 mPa·s, alternatively in the range of 1 to 1,500 mPa·s, or alternatively in the range of 1 to 1,000 mPa·s. It is noted herein that viscosity may be measured according to JIS K7117-1: Plastic - Resin in liquid state or as an emulsion or dispersion - Measurement of apparent viscosity by Brookfield test method or ISO 2555: Determination of the apparent viscosity of a plastic resin in liquid state or as an emulsion or dispersion by the Brookfield test method.
[0032] An exemplary commercially available polyolefin is the liquid polybutadiene Ricon available from CRAY VALLEY. ® 130, 156, and 257; Poly bd R-20LM.
[0033] The content of component (A) is not limited, but is preferably in the range of 5 to 30 mass% of the composition, alternatively in the range of 8 to 20 mass%, and alternatively in the range of 9 to 16 mass%. This is because when the content of component (A) is above the lower limit of the range described above, the curability of the composition of the present invention is good, whereas when the content of component (A) is below the upper limit of the range described above, the thermal conductivity of the cured product is good.
[0034] Component (B) is an organopolysiloxane having at least two silicon atom-bonded hydrogen atoms per molecule. The organic groups within the organopolysiloxane for component (B) are exemplified by monovalent hydrocarbons without aliphatic unsaturated bonds, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, and other alkyl groups having 1 to 12 carbon atoms; phenyl, tolyl, xylyl, naphthyl, and other aryl groups having 6 to 12 carbon atoms, with methyl and phenyl groups being the most typical.
[0035] The organopolysiloxane for component (B) is methylphenylpolysiloxane with both ends of the molecular chain terminally blocked by dimethylhydrogensiloxy groups; a methylphenylsiloxane-dimethylsiloxane copolymer with both ends of the molecular chain terminally blocked by dimethylhydrogensiloxy groups; a methylphenylsiloxane-methylhydrogensiloxane copolymer with both ends of the molecular chain terminally blocked by trimethylsiloxy groups; a methylphenylsiloxane-methylhydrogensiloxane-dimethylsiloxane copolymer with both ends of the molecular chain terminally blocked by trimethylsiloxy groups; (CH3)2HSiO 1 / 2 Siloxane units represented by and C6H5SiO 3 / 2 Organopolysiloxane copolymer composed of siloxane units represented by; (CH3)2HSiO 1 / 2 Siloxane unit represented by, (CH3)3SiO 1 / 2 Siloxane units represented by, and C6H5SiO 3 / 2 Organopolysiloxane copolymer composed of siloxane units represented by; (CH3)2HSiO 1 / 2 Siloxane unit represented by, (CH3)2SiO 2 / 2 Siloxane units represented by, and C6H5SiO 3 / 2 Organopolysiloxane copolymer composed of siloxane units represented by; (CH3)2HSiO 1 / 2 Siloxane unit represented by, C6H5(CH3)2SiO 1 / 2 Siloxane units represented by, and SiO 4 / 2 Organopolysiloxane copolymer composed of siloxane units represented by; (CH3)HSiO 2 / 2 Siloxane units represented by and C6H5SiO 3 / 2An organopolysiloxane copolymer composed of siloxane units represented by; as well as a mixture of two or more of the above. It is advantageous for component (B) to exhibit some compatibility with component (A). Without relying on theory, incompatibility between components (A) and (B) is presumed to cause the components to separate and produce a cured product with poor physical properties. Incompatibility can be visually determined by opacity or phase separation of components (A) and (B).
[0036] The content of component (B) is present in an amount such that the cured product obtained by curing the composition has a Shore hardness of less than 80. However, when component (B) is an organopolysiloxane having two silicon atom-bonded hydrogen atoms in the molecule, it acts as a chain extender, and thus, the content of component (B) is preferably present in an amount such that the silicon atom-bonded hydrogen atoms are preferably in the range of 1 to 5 mass%, alternatively in the range of 1.5 to 4.5 mass%, or alternatively in the range of 1.5 to 4 mass%, each based on the total mass of component (A) of the composition. Component (B) is an organopolysiloxane having at least three silicon atom-bonded hydrogen atoms in the molecule, and when each silicon atom-bonded hydrogen atom is bonded to the end of the molecular chain, it acts as a crosslinking agent, and thus, the content of component (B) is preferably present in an amount such that the silicon atom-bonded hydrogen atom is preferably in the range of 1 to 5.5 mass%, alternatively in the range of 3 to 5.5 mass%, or alternatively in the range of 4 to 5.5 mass%, each based on the total mass of components (A) to (C) of the composition. Additionally, component (B) is an organopolysiloxane having at least three silicon atom-bonded hydrogen atoms in the molecule, and when each silicon atom-bonded hydrogen atom is bonded to a side chain of the molecular chain, it acts as a crosslinking agent, but its activity is low, and therefore, the content of component (B) is preferably present in an amount such that the silicon atom-bonded hydrogen atoms are preferably in the range of 1 to 10 mass%, alternatively in the range of 1 to 9 mass%, or alternatively in the range of 1 to 8 mass%, each based on the total mass of components (A) to (C) of the composition. This is because when the content of component (B) is above the lower limit of the aforementioned range, the composition can be satisfactorily cured, and when the content of component (B) is below the upper limit of the aforementioned range, a soft material is obtained.
[0037] Component (C) is a hydrosilylation reaction catalyst used to promote the curing of the composition. Examples of component (C) include platinum-based catalysts, rhodium-based catalysts, and palladium-based catalysts. Component (C) is typically a platinum-based catalyst so that the curing of the composition can be dramatically accelerated. Examples of platinum-based catalysts include platinum fine powder, chloroplatinic acid, an alcoholic solution of chloroplatinic acid, platinum-alkenylsiloxane complexes, platinum-olefin complexes, and platinum-carbonyl complexes, with platinum-alkenylsiloxane complexes being the most typical.
[0038] The content of component (C) in the composition is present in an amount such that the catalytic metal in this component is 2 ppm or more in terms of mass units with respect to the composition, preferably in the range of 2 to 500 ppm, alternatively 2 to 100 ppm, or alternatively 2 to 50 ppm. This is because when the content of component (C) is above the lower limit of the aforementioned range, the composition is sufficiently hardened, and when the content of component (C) is below the upper limit of the aforementioned range, the heat resistance of the hardened product is improved.
[0039] Component (D) is at least one thermally conductive filler. For example, component (D) may be any combination of any one or more thermally conductive fillers selected from metals, alloys, nonmetals, metal oxides, metal hydroxides, or ceramics. Exemplary metals include, but are not limited to, aluminum, copper, silver, zinc, nickel, tin, indium, and lead. Exemplary nonmetals include, but are not limited to, carbon, graphite, carbon nanotubes, carbon fibers, graphene, and silicon nitride. Exemplary metal oxides, metal hydroxides, and ceramics include, but are not limited to, alumina, aluminum hydroxide, aluminum nitride, boron nitride, zinc oxide, and tin oxide. Preferably, component (D) is any combination of any one or more selected from the group consisting of alumina, aluminum, zinc oxide, boron nitride, aluminum nitride, and aluminum oxide trihydrate. More preferably, component (D) is any one or any combination or more of fillers selected from aluminum oxide particles having an average size of less than 5 μm, aluminum oxide particles having an average particle size of 5 μm or more, aluminum hydroxide particles having an average size of less than 5 μm, and aluminum hydroxide particles having an average particle size of 5 μm or more. Depending on the operating software, the average particle size of the filler particles as the median particle size (D50) is determined using a laser diffraction particle size analyzer (CILAS920 particle size analyzer or Beckman Coulter LS 13 320 SW).
[0040] The content of component (D) is not limited, but is preferably 50 mass% or more of the composition, preferably in the range of 70 to 95 mass%, alternatively in the range of 75 to 90 mass%, and alternatively in the range of 80 to 90 mass%. This is because the thermal conductivity of the cured product is good when the content of component (D) is below the upper limit of the range described above.
[0041] The composition may further include a filler treatment agent (E) to help disperse component (D) in component (A). Component (E) is not limited, but is preferably a silicon-based coupling agent, a titanium-based coupling agent, or an aluminum-based coupling agent.
[0042] Silicon-based coupling agents are preferably alkoxysilane compounds represented by the following general formula:
[0043] R 1 a R 2 b Si(OR 3 ) (4-a-b)
[0044] In the chemical formula, R 1 is an alkyl group having 6 to 15 carbons independently. Exemplary alkyl groups include hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl groups.
[0045] In the chemical formula, R 2 is independently an alkyl group having 1 to 5 carbons or an alkenyl group having 2 to 6 carbons. Exemplary alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and neopentyl groups. Exemplary alkenyl groups include vinyl, allyl, butenyl, pentenyl, and hexenyl groups.
[0046] In the chemical formula, R 3 is an alkyl group having 1 to 4 carbons independently. Exemplary alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, and tert-butyl groups.
[0047] In the chemical formula, "a" is an integer from 1 to 3 and "b" is an integer from 0 to 2, provided that "a + b" is an integer from 1 to 3, alternatively "a" is 1 and "b" is an integer of 0 or 1, or alternatively "a" is 1 and "b" is 0.
[0048] An exemplary silicon-based coupling agent for component (E) comprises hexyl trimethoxysilane, heptyl trimethoxysilane, octyl triethoxysilane, decyl trimethoxysilane, dodecyl trimethoxysilane, dodecyl methyl dimethoxysilane, dodecyl triethoxysilane, tetradecyl trimethoxysilane, octadecyl trimethoxysilane, octadecyl methyl dimethoxysilane, octadecyl triethoxysilane, nonadecyl trimethoxysilane, and any combination of at least two of these.
[0049] Exemplary titanium-based coupling agents for component (E) are isopropyltriisostearoyl titanate, isopropyltris(dioctylpyrophosphate)titanate, isopropyltri(N-amidoethyl, aminoethyl)titanate, tetraoctylbis(ditridecylphosphate)titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphate titanate, bis(dioctylpyrophosphate)oxyacetate titanate, bis(dioctylpyrophosphate)ethylene titanate, isopropyltrioctanoyl titanate, isopropyldimethacrylisostearoyl titanate, isopropyltridodecylbenzenesulfonyl titanate, isopropylisostearoidiacryl titanate, isopropyltri(dioctylphosphate)titanate, isopropyltricumylphenyl titanate, and It includes tetraisopropylbis(dioctylphosphite) titanate.
[0050] An exemplary aluminum-based coupling agent for component (E) includes alkylacetoacetate aluminum di-isopropylate.
[0051] The amount of component (E) is not limited, but is preferably 1 mass% or less of the composition, alternatively in the range of 0.01 to 1 mass%, or alternatively in the range of 0.1 to 1 mass%. This is because when the content of component (E) is above the lower limit of the range described above, the dispersion of component (B) in the composition is good, whereas when the content of component (E) is below the upper limit of the range described above, the stability of the composition is good.
[0052] The composition may further include additional components, such as one or more additives. Such additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers, such as TiO2 or CaCO3, opacifiers, nucleating agents, pigments, processing aids, UV stabilizers, anti-blocking agents, slip agents, adhesives, flame retardants, antimicrobial agents, odor reducers, antifungal agents, and combinations thereof.
[0053] The present composition can be prepared by combining all components at ambient temperature. Any mixing technique and apparatus described in the prior art may be used for this purpose. The specific apparatus used will be determined by the viscosity of the components and the final composition. Cooling of the components during mixing may be desirable to avoid premature curing.
[0054] In addition, to improve storage stability, the present composition is preferably a two-component type curable polyolefin composition formed from part A containing component (A), component (C), and component (D) but not component (B), and part B containing component (A), component (B), and component (D) but not component (C). It is noted that component (E) and other additional components may be contained in one or both of part A and part B.
[0055] The viscosity of the composition at 25°C is not limited; however, when the composition is separated into parts A and B, the viscosity of each of parts A and B is preferably 300 Pa·s or less. This is because excellent processability of the obtained composition is obtained when the viscosity of each of parts A and B is 300 Pa·s or less. Each viscosity is measured on a rotational rheometer ARES-G2 having a shear of 10 (1 / s), a plate diameter of 25 mm, and a gap of 0.6 mm.
[0056] The cured product of the present invention will be described in detail.
[0057] The cured product of the present invention is obtained by curing the curable polyolefin composition described above. The cured product has a Shore hardness of less than 80.
[0058] The thermal conductivity of the cured product is not limited, but preferably 1 W / mK or higher, alternatively 1.5 W / mK or higher, or alternatively 2 W / mK or higher.
[0059] This cured product is applied to various uses. In particular, it is preferably used as a thermally conductive material between the battery and the heat sink in electric vehicles.
[0060] Examples
[0061] The curable polyolefin composition and cured product of the present invention will be described in detail below using examples and comparative examples. However, the present invention is not limited by the description of the examples listed below.
[0062] <Viscosity of Part A and Part B for Curable Polyolefin Compositions>
[0063] The viscosity of each part A and part B for the curable polyolefin composition was measured by a rotational rheometer ARES-G2, where the shear is 10 (1 / s), the plate diameter is 25 mm, and the gap is 0.6 mm.
[0064] Hardness of the hardened product
[0065] Each curable polyolefin composition was poured into an aluminum pan and left at room temperature for 24 hours. After curing, each cured product was tested using a Shore OO hardness tester and a Shore A hardness tester according to ASTM D 2240.
[0066] <Thermal Conductivity (TC) of Hardened Product>
[0067] The thermal conductivity of the cured product was measured according to ISO 22007-2:2015 (Test Method for Determining Thermal Conductivity) using a Hot Disk Instant Technology Sensor C5501 (Hot Disk AB, Gothenburg, Sweden), heating time, and power of 5 s / 100 mW. After curing, the cured product was placed in two cups, and a planar sensor was placed between the cured products. A fine-tuned analysis with temperature drift compensation and time correction selected from points 10 to 190 was used.
[0068] [Examples 1 to 9 and Comparative Examples 1 to 8]
[0069] The curable polyolefin composition shown in Table 1 was prepared using the components mentioned below. First, components (A), (D), and (E) were uniformly mixed at room temperature. Then, components (B) and (C) were added to parts A and B of the mixture, respectively. Parts A and B were mixed in a 1:1 ratio in a speed mixer at 1000 rpm for 20 seconds. The final compounding was used as the curable polyolefin composition for testing.
[0070] The following ingredient was used as ingredient (A).
[0071] Ingredient (a-1): Liquid polybutadiene (Trademark: Ricon) ® 130, commercially available from TOTAL CRAY VALLEY; viscosity at 25°C = 750 mPa·s; Mn = 2,500; 1,2-vinyl content = 28%)
[0072] The following component was used as a polyolefin for comparison with component (A).
[0073] Ingredient (a-2): Liquid polybutadiene (Trademark: Ricon) ®131, Commercially available from TOTAL CRAY VALLEY; Viscosity at 25°C = 2,750 mPa·s; Mn = 4,500; 1,2-vinyl group content = 28%)
[0074] The following ingredient was used as ingredient (B).
[0075] Component (b-1): Dimethylhydrogensiloxy-terminated dimethylpolysiloxane (content of silicon atoms-bonded hydrogen atoms = 0.15 mass%)
[0076] Component (b-2): Tetrakis(dimethylsilyl) silane (content of silicon atoms-bonded hydrogen atoms = 1.23 mass%)
[0077] Component (b-3): Dimethylsiloxy-terminated dimethylpolysiloxane methylhydrogensiloxane copolymer (content of silicon atoms-bonded hydrogen atoms = 0.78 mass%)
[0078] The following component was used as component (C).
[0079] Component (c-1): 1,3-divinyl-1,1,3,3-tetramethyldisiloxane solution of Pt complex with 1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Pt atom content = 5,000 ppm)
[0080] Component (c-2): Hexadiene solution of Pt complex with 1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Pt atom content = 5,000 ppm)
[0081] The following ingredient was used as ingredient (D).
[0082] Component (d-1): Alumina filler with an average particle diameter of 0.44 μm (Trade name: AES-12, commercially available from SUMITOMO CHEMICAL COMPANY. LIMITED)
[0083] Component (d-2): Subrounded alumina filler with an average particle diameter of 35 μm (Trademark: ACF-6, commercially available from Chalco’s Zhangzhou Laboratory in China)
[0084] Component (d-3): Hydroxy aluminum filler having an average particle diameter of 0.8 to 1.2 μm (trademark: KH-101, commercially available from KC Corporation)
[0085] Component (d-4): Hydroxy aluminum filler with an average particle diameter of 25 μm (Trademark: SH-25B, commercially available from KC Corporation)
[0086] The following ingredient was used as ingredient (E).
[0087] Ingredient (e-1): n-decyl trimethoxysilane
[0088] [Table 1]
[0089]
[0090] [Table 1]
[0091]
[0092] [Table 1]
[0093]
[0094] [Table 1]
[0095]
[0096] [Table 1]
[0097]
[0098] [Table 1]
[0099]
[0100] As shown in Table 1, the compositions of Examples 1 to 9 were cured to form a soft material having a Shore hardness of less than 80 and good thermal conductivity. In contrast to the compositions of Examples 1 to 4, the comparative compositions of Comparative Examples 1 and 2 were not cured due to the lack of component (C) and the lack of component (B).
[0101] As shown in Table 1, in contrast to the compositions of Examples 1 to 4, the comparative compositions of Comparative Examples 3 and 4 could not form a soft material due to overloading of component (B). In the same way, in contrast to the compositions of Examples 5 to 8, the comparative composition of Comparative Example 5 could not form a soft material due to overloading of component (B). And in the same way, in contrast to the compositions of Examples 1 to 4 and Example 9, the comparative compositions of Comparative Examples 6 and 7 could not form a soft material due to overloading of component (B).
[0102] As shown in Table 1, in contrast to the composition of Example 9, the comparative composition of Comparative Example 8 could not form a soft material because the polyolefin for component (A) had a viscosity of 2,500 Pa·s or higher at 25°C. Meanwhile, in the comparative composition of Comparative Example 8, the viscosity of each of part A and part B was greater than 300 Pa·s. Industrial applicability
[0103] The curable polyolefin composition of the present invention can be cured to form a soft material having good thermal conductivity properties. Therefore, the curable polyolefin composition is useful as a thermal management material for batteries in electric vehicles.
Claims
Claim 1 A curable polyolefin composition comprising: (A) a polybutadiene having at least two aliphatic unsaturated bonds per molecule and a viscosity of less than 2,500 mPa·s at 25°C; (B) an organopolysiloxane having at least two silicon atom-bonded hydrogen atoms per molecule in an amount such that the cured product obtained by curing the composition has a Shore hardness of less than 80; and (C) a hydrosilylation reaction catalyst selected from platinum-based catalysts, rhodium-based catalysts, and palladium-based catalysts, in an amount such that the catalytic metal in this component is at least 2 ppm in terms of mass with respect to the composition. A curable polyolefin composition comprising (D) a thermally conductive filler selected from metals, alloys, nonmetals, metal oxides, metal hydroxides, and ceramics, wherein the content of component (B) is an amount such that, based on the total mass of components (A) to (C), the silicon atom-bonded hydrogen atom is in the range of 1 to 10 mass%. Claim 2 A curable polyolefin composition according to claim 1, wherein the content of component (D) is 50 mass% or more of the composition. Claim 3 A curable polyolefin composition according to claim 1, wherein (E) additionally comprises a filler treatment agent, said filler treatment agent is selected from silicon-based coupling agents, titanium-based coupling agents, and aluminum-based coupling agents. Claim 4 A curable polyolefin composition according to claim 3, wherein the content of component (E) is 1 mass% or less of the composition. Claim 5 A cured product obtained by curing a curable polyolefin composition described in any one of claims 1 to 4, the cured product having a Shore hardness of less than 80. Claim 6 In paragraph 5, a hardened product used between a battery and a heat sink in an electric vehicle. Claim 7 delete Claim 8 delete
Citation Information
Patent Citations
Polymer electrolyte fuel-cell separator sealing rubber composition
US20030045615A1
Rubber Compound
US20080315148A1
Hydrosilylation Curable Compositions
US20100206477A1
Silicone composition
US20210079221A1
Curable composition for heat conductive material
US20030160207A1
